1993
DOI: 10.1007/bf00276883
|View full text |Cite
|
Sign up to set email alerts
|

Rapid divergence of Agrobacterium vitis octopine-cucumopine Ti plasmids from a recent common ancestor

Abstract: The octopine/cucumopine (o/c) Ti plasmids of the grapevine-associated Agrobacterium vitis strains constitute a family of related DNA molecules. Restriction maps were established of two limited-host-range o/c Ti plasmids, pTiAg57 and pTiAB3, and of the wide-host-range o/c Ti plasmid pTiHm1. Together with the previously obtained map of the wide-host-range o/c Ti plasmid pTiTm4, about 1000 kb were mapped with a resolution of 0.2 kb, allowing a detailed comparison of the various structures. One region of the o/c T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…Ti plasmids from the six A. tumefaciens and eight A. vitis strains analyzed here were previously characterized to some extent at the DNA level, but inducibility of virulence genes by acetosyringone and production of virulence proteins were not analyzed in most cases (24,35,46). Antisera raised by immunization with C58-specific proteins allowed the detection of most virulence proteins in the acetosyringone-induced A. tumefaciens strains (except VirB3, VirB6, and VirD4) and of four virulence proteins in the acetosyringone-induced A. vitis strains (VirB5, VirB7, VirB8, and VirB9).…”
Section: Discussionmentioning
confidence: 99%
“…Ti plasmids from the six A. tumefaciens and eight A. vitis strains analyzed here were previously characterized to some extent at the DNA level, but inducibility of virulence genes by acetosyringone and production of virulence proteins were not analyzed in most cases (24,35,46). Antisera raised by immunization with C58-specific proteins allowed the detection of most virulence proteins in the acetosyringone-induced A. tumefaciens strains (except VirB3, VirB6, and VirD4) and of four virulence proteins in the acetosyringone-induced A. vitis strains (VirB5, VirB7, VirB8, and VirB9).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, several other methods have been used to characterize A. vitis. (65,104) but differ in other regions. and 150 strains of Rhizobium and Sinorhizobium.…”
Section: Agrobacterium Vitismentioning
confidence: 90%
“…Jarvis et al (48) used fatty acid analysis to identify species of 65 strains of Agrobacterium spp. Interestingly, the nucleotide sequences of common regions are more than 99.9% homologous, which suggests that the evolution of plasmids proceeds mainly by large-scale events like insertions and deletions (65,71,104). A two-dimensional plot analysis of fatty acid compositions revealed that A. vitis is more similar to Rhizobium galegae than it is to other A. tumefaciens or A. rhizogenes.…”
Section: Agrobacterium Vitismentioning
confidence: 99%
“…Interestingly, the genetic detenninants involved in opine degradation are most often borne on the Ri plasmids. These studies indicate that Ti plasmids have probably evolved as "mosaic" structures, composed of conserved regions (the T -DNA, the virulence genes) and variable regions such as those determining opine degradation (paulus et aI., 1991aVan Nuenen et al, 1993;Otten and De RufIray, 1994). rhizogenes (petit et al, 1983;Jouanin, 1984;Hufmann et al, 1984;Jouanin et al, 1986).…”
Section: Conceptmentioning
confidence: 99%